Factor hindering the implementation of qlassic in Malaysian construction industry - Nor Ain Zamiza, Ahmad Salhar (2018)
CIDB has introduced Quality Assessment System in Construction (QLASSIC) in 2006 to help increasing the quality of building in Malaysia. After more than 10 years QLASSIC has been introduced, there are still many developers and contractors unfamiliar with QLASSIC. This has led to the main objective of conducting this research, namely to identify the factor hindering the implementation of QLASSIC in Malaysia. This research had utilized questionnaire form as the research instrument. The respondents for this research were construction personnel from developer’s company and contractor’s company. The data collected were then analyzed by using Relative Importance Index (RII). The research outcomes can provide understanding in the principle and concept of QLASSIC, list of factors hindering the implementation of QLASSIC and lastly analysis of the most significant factor hindering the implementation of QLASSIC in Malaysia. In general, this research revealed five factors hindering the implementation of QLASSIC in Malaysia. The factors were advertisement efficiency, time constraint, cost constraint, behavior of construction player and insufficient skilled worker. In addition, this research shown that the most crucial factor hindering the implementation of QLASSIC in Malaysian construction industry was the behavior of construction player. The behavior of construction players included resist to adopt new approach, reluctant to attend any training to enhance their knowledge in QLASSIC, reluctant to change, construction player tend to reduce the perceived risk in adopting a new approach and a new approach will create a new role so they afraid it will take their role. The most crucial factor hindering the implementation of QLASSIC in Malaysia then was followed by time constraint factor, advertisement efficiency factor, cost constraint factor and insufficient skilled worker factor. In a nutshell, government has to make a new strategy to address this issue if government wants to see the construction industry in Malaysia able to compete globally and Malaysian construction players such as developers and contractors must change their behavior by be more open with new approaches suggested by government.